THE USE OF GRAMMAR-TRANSLATION METHOD TO TEACH READING TO THE TENTH CLASS STUDENTS AT SMK YPM 12 TUBAN ACADEMIC YEAR 2020/2021 - Ali Fauzi (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
English is the first foreign language in Indonesia which is considered important in transferring and developing science and technology, arts and building the relationship among countries. Based on the 1994 basic course outline, the purpose of English teaching at Technical Senior High Schools is to develop the four language skills: listening, speaking, reading and writing. The teaching of those four language skills can be done in integrative way in which the emphasis is on developing the students’ reading skill. The less attention to a certain language skill may cause the students’ unbalanced mastery of English. However, teaching reading using certain method like grammar-translation method is also important because by it students will be able to understand the English text, grammar and structure and translation well through which they will be a means of improving other skills such as speaking. From the reasons, the researcher wants to study about The Use of Grammar-Translation Method to Teach reading to the Tenth Class Students at SMK YPM 12 Tuban Academic Year 2020/2021. This title is chosen because he is sure that reading is also important besides speaking, writing and listening. This study is in form of descriptive analysis which means that he describes what he finds in the real life and he reveals them to prove the rightness of his assumption. He tries to find the data and process them and just describes his finding. He analyzes and describes about the use of grammar-translation method in teaching reading and the problems the teacher and students face in the process of teaching and learning. Besides them, it is also prominent to tell the process or activities in the teaching of reading using grammar-translation method. It is hoped that some alternatives to solve these problems can be found. Therefore it is expected that this study will be useful for English teacher as the alternative method to teach reading, for the readers to add their knowledge about different ways in teaching reading and for the students in general to be the reference to add their knowledge and to do further research.